2020
DOI: 10.3389/fpubh.2020.576964
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Triple Negative Breast Cancer: A Review of the Role of Biologic and Non-biologic Factors

Abstract: Triple-negative breast cancer (TNBC) is an aggressive subtype of breast cancer that lacks expression of the estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor (HER2). TNBC constitutes about 15–30 percent of all diagnosed invasive breast cancer cases in the United States. African-American (AA) women have high prevalence of TNBC with worse clinical outcomes than European-American (EA) women. The contributing factors underlying racial disparities have been divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 145 publications
2
67
0
1
Order By: Relevance
“…Samples were collected from patients of various age groups (Fig 1C ) and diverse ethnic and racial backgrounds (Fig 1D). An increased proportion of TNBC tumor samples was observed from black patients with African or west-Indian heritage (Fig 1D,Table S1) which recapitulates the higher incidence of TNBCs in the African-American community (Perou, 2011;Prakash et al, 2020). Using a DNA-seq panel of 143 cancer driver genes, we identified pathogenic single nucleotide variants (SNVs) in 45 tumor organoid lines (Fig 1E ); PIK3CA was mutated in 33% of the tumor organoids, the majority of which were from patients with luminal breast cancer.…”
Section: Resultssupporting
confidence: 53%
“…Samples were collected from patients of various age groups (Fig 1C ) and diverse ethnic and racial backgrounds (Fig 1D). An increased proportion of TNBC tumor samples was observed from black patients with African or west-Indian heritage (Fig 1D,Table S1) which recapitulates the higher incidence of TNBCs in the African-American community (Perou, 2011;Prakash et al, 2020). Using a DNA-seq panel of 143 cancer driver genes, we identified pathogenic single nucleotide variants (SNVs) in 45 tumor organoid lines (Fig 1E ); PIK3CA was mutated in 33% of the tumor organoids, the majority of which were from patients with luminal breast cancer.…”
Section: Resultssupporting
confidence: 53%
“…The relationship between BRCA1 mRNA levels and frequency of African American patients was statistically significant based on a Fisher’s exact test of the contingency table shown in Supplementary Table 1. As African American women are more likely to get BC (particularly TNBC) [ 26 ], this result is surprising because we found that low expression of BRCA1 mRNA correlated with better outcomes in BC ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 80%
“…For example, the gene signatures that define breast cancer subtypes have shaped our approaches to developing research for targeted therapies; however, we also find that gene signatures have significant variation across patient groups, underlying a bias in the incidence of specific subtypes within these patient groups. Specifically, we now know that triple-negative breast cancers (TNBC) are more prevalent in non-White populations (12) and that the subtypes of TNBC, defined by the genomic signature of hundreds of genes, also show significant bias among race groups (13). Yet, knowing this does not necessarily change the course of treatment.…”
Section: Diagnostic Genomicsmentioning
confidence: 99%